Islamic religious education teachers' parenting in developing children's religious character at Randublatung - Lathifatul Ismi Fauziah; Ridwan Ridwan; Agus Sutiyono; Nazih Sadatul Kahfi (Himpunan Pengembang Kurikulum Indonesia, 2025)
The decline in children's religious character is a pressing social issue that warrants serious attention. Parents, especially those who work as Islamic Religious Education (PAI) teachers, have a strategic role in shaping children's religious character. This study aims to explore the parenting patterns of PAI teachers in instilling religious values in the Randublatung District, Blora Regency. The method employed was qualitative, with a phenomenological approach, utilizing interview techniques, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that parents who are also PAI teachers apply authoritative and authoritarian parenting, with an emphasis on role modelling, open communication, and disciplinary supervision. They serve as moral and spiritual figures who can positively influence children's religious awareness. The application of the habituation method in daily life has proven effective in shaping children's religious character, particularly in terms of discipline in worship and the internalization of moral values. This study recommends further development with a broader sample coverage and consideration of socio-economic variables in the context of religious parenting. Abstrak Menurunnya karakter religius anak menjadi isu sosial yang memerlukan perhatian serius. Orang tua, khususnya yang berprofesi sebagai guru Pendidikan Agama Islam (PAI), memiliki peran strategis dalam pembentukan karakter religius anak. Penelitian ini bertujuan mengeksplorasi pola asuh guru PAI dalam menanamkan nilai religius di Kecamatan Randublatung, Kabupaten Blora. Metode yang digunakan adalah kualitatif dengan pendekatan fenomenologi, melalui teknik wawancara, observasi, dan dokumentasi. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa orang tua yang juga guru PAI menerapkan pola asuh otoritatif dan otoriter, dengan penekanan pada keteladanan, komunikasi terbuka, serta pengawasan disiplin. Mereka berperan sebagai figur moral dan spiritual yang mampu memberikan pengaruh positif terhadap kesadaran beragama anak. Penerapan metode pembiasaan dalam kehidupan sehari-hari terbukti efektif membentuk karakter religius anak, terutama dalam hal kedisiplinan beribadah dan internalisasi nilai-nilai moral. Penelitian ini merekomendasikan pengembangan studi lebih lanjut dengan cakupan sampel yang lebih luas serta mempertimbangkan variabel sosial-ekonomi dalam pola asuh religius. Kata Kunci: gaya pengasuhan; guru PAI; karakter religius